Meningkatkan Kinerja UMKM Melalui Pemasaran Digital untuk Meningkatkan Produk Perusahaan - Yayan Listanto Alexander (STKIP PGRI SITUBONDO, 2023)
This study aims to reveal several digital marketing strategies for baby clothes products and prove the efficiency of improving MSME performance through digital marketing. This research uses descriptive qualitative method. The power needed as a research knife is primary data that the author obtained by observing and interviewing parties related to this research. Secondary data was obtained from various books, journal articles, and other supporting literature. While the results of this study are: first, based on the opinion of MSME business owners who improve their performance through digital marketing by simply creating content that is interesting and easy for people to remember. Second, based on the opinions of MSME enthusiasts and customers, this